التفسير العلمي للقرآن بإندونيسيا: منهجه وتطبيقاته - Nuha, Ulin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
This research is aimed at looking at scientific interpretation method in Indonesia and its application. The literature that is the object of this research is a book entitled Time in the Perspective of the Qur'an and Science which was written by a group of ulama and scientists from Lajnah Pentashihan Mushaf al-Qur'an and the Indonesian Institute of Sciences (LIPI). This research belongs to the type of library research, where the data source is obtained from books and papers. In analyzing research objects, the author uses the formulation of the scientific interpretation method written by Abdul Jabbar Saqa and the author of the book Time in the Perspective of the Qur'an and Science. From the results of this research, it was found that the book Time in the Perspective of the Qur'an and Science was written by popular scholars in Indonesia: tafsir scholars and scientists. From all the descriptions it is understood that this book pays attention to aspects of linguistic rules, al-Qur'an sciences, and the interpretations of previous scholars. This book of tafsir also separates interpretation and scientific findings, both of which are different. Scientific findings are not interpretations of the Qur'an, but are part of the expansion of the Qur'an's instructions where changes to the findings will not affect the sanctity of the Qur'an.